Self-Enforcing Family Rules, Marriage and the (Non)Neutrality of Public Intervention - Alessandro Cigno; Mizuki Komura; Annalisa Luporini (Center for Economic Studies and ifo Institute (CESifo), 2016)
We demonstrate that the notion of a “family constitution” (self-enforcing, renegotiation-proof family norm) requiring adults to provide attention for elderly parents carries over from a world where sexually indifferentiated individuals reproduce by cell separation, to one where individuals differentiated by sex marry, have children and bargain over the allocation of domestic resources on condition that individual preferences are transmitted from parents to children, and having the same preferences is a criterion for marrying. We also show that policies are generally nonneutral (even if the individuals concerned are altruistically linked to one another) and affect the share of the adult population that are governed by family constitutions.
Keywords: D10; I20; I30; J10; 330; marriage; family constitution; preference transmission; policy neutrality